Advantages of using a cooler bypass in the low-pressure exhaust gas recirculation line of a compression ignition diesel engine operating at cold conditions. (May 2021) - Galindo, José; Dolz, Vicente; Monsalve-Serrano, Javier; Bernal Maldonado, Miguel Angel; Odillard, Laurent
The low efficiency of the after-treatment systems during the cold start period of the internal combustion engines leads to excessive pollutant emissions levels. To reduce the nitrogen oxide emissions at these conditions, it could be necessary to use the high- and low-pressure exhaust gas recirculation strategies, even operating at low temperatures. This article evaluates the impact of using a low-pressure exhaust gas recirculation cooler bypass in a Euro 6 turbocharged diesel engine running under cold conditions (–7 °C). A new compact line fitted with a bypass system for the cooler is used with the aim of accelerating the engine warm-up process as compared to the original low-pressure exhaust gas recirculation line. The system is evaluated following two strategies, first performing exhaust gas recirculation without bypass and then performing exhaust gas recirculation bypassing the cooler. The results show that the activation the low-pressure exhaust gas recirculation from the engine cold start leads to a significant nitrogen oxide emissions reduction. Moreover, the bypass activation leads to increase the engine intake temperature, reducing the engine warm-up time and the CO emissions due to better combustion efficiency. However, the activation of the low-pressure exhaust gas recirculation at low temperatures could produce condensation and fouling deposits on the engine components affecting their life span. These phenomena are visualized using endoscope cameras in order to identify the condensation time and the final conditions of the elements. In addition, a chemical analysis of some condensates collected during the experiments and a comparison versus other species found in the literature is presented.